1967
DOI: 10.1037/h0025070
|View full text |Cite
|
Sign up to set email alerts
|

Stability of cognitive style from childhood to young adulthood.

Abstract: DEVELOPMENT OF DIFFERENTIATION, AS REFLECTED IN COGNITIVE STYLE, WAS FOLLOWED LONGITUDINALLY IN 2 GROUPS, 1 FROM 8-13 YR., THE OTHER FROM 10-24 YR. A BATTERY OF TESTS OF FIELD DEPENDENCE WAS USED TO EVALUATE EXTENT OF DIFFERENTIATION IN PERCEPTUAL FUNCTIONING. COMPARABLE CROSS-SECTION DATA WERE OBTAINED FROM GROUPS IN THE SAME AGE RANGE. A PROGRESSIVE INCREASE IN EXTENT OF FIELD INDEPENDENCE IS EVIDENT UP TO AGE 17, WITH NO FURTHER CHANGE FROM 17-24. WITHIN THIS GENERAL DEVELOPMENT TREND, CHILDREN SHOW MARKED … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
135
1
9

Year Published

1969
1969
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 309 publications
(162 citation statements)
references
References 8 publications
17
135
1
9
Order By: Relevance
“…We assessed verbal mental age because, as discussed, previous research has shown a strong positive association between verbal mental age and theory-of-mind success in children (see Yirmiya et al, 1998). Similarly, speed on the Embedded Figures Test has been shown to increase with development and to be related to children's level of verbal ability (Coates, 1972;Witkin, Goodenough, & Karp, 1967;Witkin et al, 1971). The importance of these points is that the links between age and general intelligence on the one hand, and theory of mind and Embedded Figures Test speed on the other, might mask the hypothesized inverse relationship between theory of mind and central coherence unless individual differences in age and intelligence are accounted for in a developmental sample.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed verbal mental age because, as discussed, previous research has shown a strong positive association between verbal mental age and theory-of-mind success in children (see Yirmiya et al, 1998). Similarly, speed on the Embedded Figures Test has been shown to increase with development and to be related to children's level of verbal ability (Coates, 1972;Witkin, Goodenough, & Karp, 1967;Witkin et al, 1971). The importance of these points is that the links between age and general intelligence on the one hand, and theory of mind and Embedded Figures Test speed on the other, might mask the hypothesized inverse relationship between theory of mind and central coherence unless individual differences in age and intelligence are accounted for in a developmental sample.…”
Section: Discussionmentioning
confidence: 99%
“…in their characteristic mode of perceiving (Bauman, 1951;Witkin et a1., 1954;Witkin, Goodenough & Karp, 1967). I should also point out that there are sex differences in field dependence.…”
Section: The Nature Of Cognitive Stylesmentioning
confidence: 99%
“…-25-A study in which we followed the same children over the 10-to 24-year-age period showed that an individual's standing on the field-dependence-independence cognitive'style remains relatively stable over this age period (Witkin, et al, 1967). This observation makes it reasonable to believe that the cognitive assessments we made at the time of their admission into college is likely to reflect our students' cognitive makeup both in the earlier high-school period and in the later graduate-school period.…”
Section: Cognitive Style As a Factor In Academic Evolutionmentioning
confidence: 99%
“…Error bars illustrate standard errors. Goodenough, and Karp (1967) showed that the ability to ignore the visual context in perceptual judgments-known as field independence-is a stable cognitive style from childhood to young adulthood, at least. Furthermore, Couch and Keniston (1960) investigated acquiescence bias in terms of consistency over time and generality over tests.…”
mentioning
confidence: 99%